Legal Implications of Building Use Rights Certificates Without Land Status Information: Consumer Protection and the Responsibility of the National Land Agency : - Ibnu Sani, Rijal; Suartini, Suartini (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: This research examines the legal uncertainties arising from the issuance of Building Use Rights (HGB) certificates on land with Management Rights (HPL) owned by the Special Capital Region of Jakarta. The lack of clarity in the National Land Agency's certificate, which does not explicitly state that the building use rights are based on land management rights, leads to confusion and a sense of deception among consumers, making this issue crucial. This issue holds significant importance as the National Land Agency's certificate, which does not explicitly state that building use rights are based on land management rights, leads to consumer confusion and feelings of deception. When consumers applied for a certificate extension 20 years after the National Land Agency issued the Certificate Extension Decision Letter, the agency abruptly retracted both the Decision Letter and the certificate. This was due to the BPN's recent realization that the land was under Land Management Rights. This research uses a normative juridical approach to analyze the legal responsibility of the National Land Agency in the issuance of certificates. The data collection technique uses document studies, while the analysis technique uses court decision studies. Research results indicate that Building Use Rights (HGB) certificates that do not specify the type of land—whether it is on state land, Land Management Rights, or ownership rights—have the potential to harm consumers and cause legal disputes. Therefore, this study recommends land policy reforms to ensure legal certainty and consumer rights protection in property transactions. Keywords: Building Use Rights, Land Management Rights, Land Certificate, Legal Certainty, National Land Agency